Dividend Payout Ratio and Shareholder Return : Evidence from Helsinki Stock Exchange - Viljami, Riuttala (My University, 2025)
This study examines the relationship between the dividend payout ratio and total return in Finnish companies listed on the Helsinki Stock Exchange during the years 2003–2024. The analysis employs simplified and extended fixed-effects models that account for both firm- and year-specific effects. As a third model, an extended specification introduces that excludes firm-specific effects but includes sector-specific effects. The dependent variable is total return (%), and the key explanatory variable is the lagged dividend payout ratio (t–1). The control variables include free cash flow, market capitalization, the book-to-market ratio, leverage, and a sector variable. Shareholder returns indicate that companies paying dividends are performed better than non-dividend-paying companies. However, when the dividend payout ratio and control variables are taken into account, dividend distribution itself is not a statistically significant explanatory factor. The simplified model shows a statistically significant negative relationship: a one-percentage-point increase in the dividend payout ratio decreases total return by 0.163 percentage points (p = 0.0001). The result of the extended model is not significant (p = 0.6793). In the sector-specific extended model, the results are significant, indicating an inverted U-shaped relationship and showing that a dividend payout ratio of 33.9% would be optimal, after which the relationship between shareholder return and the payout ratio turns negative. The robustness checks employ winsorization of extreme values, removal of control variables, and a separate examination of the post-financial-crisis period. These confirm the stability of the results.

Tässä tutkimuksessa tarkastellaan osingonjakosuhteen ja kokonaistuoton välistä suhdetta suomalaisissa Helsingin pörssiin listatuissa yhtiöissä vuosina 2003–2024. Analyysissa hyödynnetään pelkistettyä ja laajennettua kiinteiden vaikutusten malleja, joissa huomioidaan sekä yritys- että vuosikohtaiset vaikutukset. Kolmantena mallina tuodaan laajennettu malli, jossa ei ole yrityskohtaisia vaikutuksia, mutta on huomioitu toimialakohtainen vaikutus. Selitettävänä muuttujana on kokonaistuotto (%), ja keskeisenä selittävänä muuttujana käytetään viivästettyä osingonjakosuhdetta (t–1). Kontrollimuuttujina käytetään vapaata kassavirtaa, markkina-arvoa, kirjanpidollisen arvon suhdetta markkinahintaan, velkaantuneisuusastetta sekä toimialamuuttujaa. Yhtiöiden osakkeenomistajien tuotot osoittavat, että osinkoa maksaneet yhtiöt ovat tuottaneet paremmin kuin osingottomat yhtiöt. Kun kuitenkin huomioidaan osingonjakosuhde ja kontrollimuuttujat, itse osingonjako ei ole tilastollisesti merkitsevä selittäjä. Pelkistetty malli osoittaa tilastollisesti merkitsevän negatiivisen yhteyden: yhden prosenttiyksikön kasvu osingonjakosuhteessa pienentää kokonaistuottoa 0,163 prosenttiyksikköä (p = 0.0001). Laajennetun mallin tulos ei ole merkitsevä (p = 0.6793). Sektorikohtiasessa laajennetussa mallissa tulokset on merkittäviä ja tämä osoittaa käänteisen u-muotoisen yhteyden, osoittaen, että 33,9% suuruinen osingonjakosuhde olisi optimi, jonka jälkeen osakkeenomistajien tuotto ja osingonjakosuhteen yhteys kääntyy negatiiviseksi. Robustisuustarkasteluissa hyödynnetään ääriarvojen winsorointia, kontrollimuuttujien poistamista sekä finanssikriisin jälkeisen ajan erillistä tarkastelua, nämä vahvistavat tulosten pysyvyyden.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance; Master’s Thesis in Finance